Case Report: An Unusual Case of Nutcracker Syndrome and Literature Review - Li, Lu; Feng, Chunyue; Shen, Huijun; Zhu, Linfeng; Fu, Haidong; Chen, Zhongyu; Gu, Weizhong; Mao, Jianhua (Frontiers in Urology, 2022)
Background: Hematuria is one of the common complaints of patients with kidney disease and often occurs concurrently with proteinuria. Hematuria caused by nutcracker syndrome (NCS) is relatively common, while hematuria caused by type I von Willebrand disease (VWD) is less common. Case presentation: A 12-year-old boy was admitted to our ward due to sudden gross hematuria that had lasted for 4 days. After admission, his gross hematuria lasted for 24 days without remission and was combined with nephrotic-range proteinuria. A series of blood biochemical and urine tests, as well as renal ultrasound, lower abdominal CT angiography, cystoscopy, kidney biopsy, and genetic testing, were completed, and he was eventually diagnosed with NCS combined with type 1 VWD. After nutritional support, oral angiotensin-converting enzyme inhibitor (ACEI), and plasma infusion treatment, gross hematuria and microhematuria disappeared, proteinuria turned negative, and there was no recurrence during the 10 months of follow-up. Conclusions: NCS and/or VWD may exist in patients with hematuria, and bleeding disorders such as VWD should generally be on the list of suspected diagnoses in patients with hematuria.